Anchoring of a Carboxyl-Functionlized Norbornadiene Derivative to an Atomically-Defined Cobalt Oxide Surface - Schwarz, Matthias; Mohr, Susanne; Xu, Tao; Döpper, Tibor; Weiß, Cornelius; Civale, Katharina; Hirsch, Andreas; Görling, Andreas; Libuda, Jörg (Journal of Chemical Physics, 2017)
We have investigated the anchoring of the molecular energy carrier norbornadiene (NBD) to an atomically defined oxide surface. To this end, we synthesized a carboxyl-functionalized NBD derivative, namely 1-(2′-norbornadienyl)pentanoic acid (NBDA), and deposited it by physical vapor deposition (PVD) under ultrahigh vacuum (UHV) conditions onto a well-ordered Co3O4(111) film grown on Ir(100). In addition, we performed a comparative growth study with benzoic acid (BA) under identical conditions which was used as a reference. The interaction and orientation of NBDA and BA with the oxide surface were monitored in situ during film growth by isothermal time-resolved infrared reflection–absorption spectroscopy (TR-IRAS), both below and above the multilayer desorption temperature. The thermal behavior and stability of the films were investigated by temperature-programmed IRAS (TP-IRAS), with help of density functional (DF) calculations. BA binds to Co3O4(111) under formation of a symmetric chelating carboxylate with the molecular plane oriented nearly perpendicular to the surface. At low temperature (130 K), intact BA physisorbs in form of dimers on top of the saturated monolayer. Upon annealing to 155 K, a reordering transition is observed, in which BA in the multilayer adopts a more flat-lying orientation. The BA multilayer desorbs at 220 K, whereas the surface-anchored BA monolayer is stable up to 400 K. At higher temperature (400–550 K), desorption and decomposition are observed. Very similar to BA, NBDA binds to Co3O4(111) by formation of a symmetric chelating carboxylate. In the multilayer, which desorbs at 240 K, hydrogen-bonded NBDA dimers are formed. Upon PVD of NBDA at 300 K, only a surface anchored carboxylate is stable. The anchored NBDA film shows a characteristic restructuring behavior as a function of coverage. At low coverage the NBDA, adopts a flat-lying structure in which the norbornadiene unit interacts with the Co3O4 surface. With increasing coverage, the norbornadiene units detach from the oxide and the NBDA adopts an upright-standing orientation. Similar to BA, the anchored film is stable up to 400 K and decomposes in the temperature region between 400 and 550 K, leaving behind hydrocarbon residues on the oxide surface.

Back Cover: Energy Storage in Strained Organic Molecules: (Spectro)Electrochemical Characterization of Norbornadiene and Quadricyclane (ChemSusChem 12/2016) - Brummel, Olaf; Besold, Daniel; Döpper, Tibor; Wu, Yanlin; Bochmann, Sebastian; Lazzari, Federica; Waidhas, Fabian; Bauer, Udo; Bachmann, Philipp; Papp, Christian; Steinrück, Hans-Peter; Görling, Andreas; et al. (ChemSusChem, 2016)
Keywords: infrared spectroscopy; norbornadiene; quadricyclane; spectroelectrochemistry; voltammetry

Benzoic Acid and Phthalic Acid on Atomically Well-Defined MgO(100) Thin Films: Adsorption, Interface Reaction, and Thin Film Growth - Xu, Tao; Mohr, Susanne; Amende, Maximilian; Laurin, Mathias; Döpper, Tibor; Görling, Andreas; Libuda, Jörg (Journal of Physical Chemistry C, 2015)
To better understand the interaction and the growth of thin films of functionalized organic molecules on oxide surfaces, we have studied the adsorption, reaction, and desorption of benzoic acid (BA) and phthalic acid (PA) on a well-ordered MgO(100) thin film grown on a Ag(100) single crystal surface. We have applied isothermal time-resolved infrared reflection absorption spectroscopy (TR-IRAS) and temperature-programmed IRAS (TP-IRAS) under ultrahigh-vacuum (UHV) conditions. BA is dosed using a supersonic molecular beam (SSMB) source while PA is deposited by physical vapor deposition (PVD). For both molecules we have explored the film growth as a function of temperature, both in the monolayer and in the multilayer regime. We have also investigated structural transitions and desorption by temperature-programmed experiments in the range from 100 to 400 K. In addition, we carried out density-functional (DF) calculations. We find that both molecules BA and PA bind through the carboxyl groups to the MgO (100) surface. Upon adsorption at 100 K BA binds in an asymmetric bidentate geometry which exhibits a small tilting angle between the aromatic plane and the surface. Beyond the monolayer, a disordered multilayer film grows, which crystallizes under formation of dimers at around 180 K as indicated by a characteristic splitting of the IR bands. The BA multilayer desorbs at 240 K. Upon adsorption at 300 K, only a BA monolayer forms. Again, BA forms an asymmetric bidentate but with a larger tilting angle compared to low-temperature adsorption. For PA adsorption at 100 K, the adsorption mechanism is observed to change with coverage. At low coverage, both carboxyl groups are deprotonated, and the molecule forms an asymmetric bis-bidentate carboxylate with the aromatic plane nearly perpendicular to the surface. At high coverage, only one carboxyl group binds to the surface and forms an asymmetric bidentate carboxylate while the molecules maintain an upright standing orientation. During PVD of PA, a small fraction of phthalic anhydride (PAA) is formed which coadsorbs at low temperature. Upon annealing, the PAA. desorbs around 250 K, triggering a structural transformation of the PA multilayer during which the PA adopts a more flat lying orientation. The PA multilayer itself desorbs around 310 K. Therefore, only monolayer of PA is stable around 300 K. Again, the adsorption mechanism is coverage dependent, changing from a bis-bidentate carboxylate at lower coverage to a monobidentate carboxylate at higher coverage.

Catalytically Triggered Energy Release from Strained Organic Molecules: The Surface Chemistry of Quadricyclane and Norbornadiene on Pt(111) - Bauer, Udo; Mohr, Susanne; Döpper, Tibor; Bachmann, Philipp; Späth, Florian; Düll, Fabian; Schwarz, Matthias; Brummel, Olaf; Fromm, Lukas; Pinkert, Ute; Görling, Andreas; Hirsch, Andreas; et al. (Chemistry - A European Journal, 2017)
We have investigated the surface chemistry of the polycyclic valence-isomer pair norbornadiene (NBD) and quadricyclane (QC) on Pt(111). The NBD/QC system is considered to be a prototype for energy storage in strained organic compounds. By using a multimethod approach, including UV photoelectron, high-resolution X-ray photoelectron, and IR reflection-absorption spectroscopic analysis and DFT calculations, we could unambiguously identify and differentiate between the two molecules in the multilayer phase, which implies that the energy-loaded QC molecule is stable in this state. Upon adsorption in the (sub)monolayer regime, the different spectroscopies yielded identical spectra for NBD and QC at 125 and 160K, when multilayer desorption takes place. This behavior is explained by a rapid cycloreversion of QC to NBD upon contact with the Pt surface. The NBD adsorbs in a η:η geometry with an agostic Pt-H interaction of the bridgehead CH subunit and the surface. Strong spectral changes are observed between 190 and 220K because the hydrogen atom that forms the agostic bond is broke. This reaction yields a norbornadienyl intermediate species that is stable up to approximately 380K. At higher temperatures, the molecule dehydrogenates and decomposes into smaller carbonaceous fragment
Keywords: Catalysis; DFT calculations; IR spectroscopy; Photoelectron spectroscopy; Surfaces and interfaces

Charge distribution analysis in Agn m+ clusters: Molecular modeling and DFT calculations - Milek, Theodor; Döpper, Tibor; Neiß, Christian; Görling, Andreas; Zahn, Dirk (Journal of Molecular Modeling, 2014)
Neutral and charged silver clusters Ag and Ag (m=0,...,20) are investigated by simulated annealing molecular dynamics simulations. With increasing charge to size ratio the clusters undergo deformation to better accommodate surface charges. The latter are heterogeneously distributed and reflect the interplay of overall electrostatic repulsion and different degrees of local under-coordination of surface atoms. By comparison with atomic charges from natural population analysis based on density-functional calculations we demonstrate the suitability of the embedded-atom force-field in combination with the charge equilibrium approach. © 2014 Springer-Verlag Berlin Heidelberg.
Keywords: DFT calculations; Metal nanoparticles; Molecular mechanics; Partial charges analysis

Coverage-Dependent Anchoring of 4,4 '-Biphenyl Dicarboxylic Acid to CoO(111) Thin Films - Mohr, Susanne; Schmitt, Tobias; Döpper, Tibor; Xiang, Feifei; Schwarz, Matthias; Görling, Andreas; Schneider, M. Alexander; Libuda, Jörg (Langmuir, 2017)
We investigated the adsorption behavior of 4,4'-biphenhyl dicarboxylic acid (BDA) on well-ordered CoO(111) films grown on Ir(100) as a function of coverage and temperature using time-resolved and temperature programmed infrared reflection absorption spectroscopy (TR-IRAS, TP-IRAS) in combination with density functional theory (DFT) and scanning tunneling microscopy (STM) under ultrahigh vacuum (UHV) conditions. To compare the binding behavior of BDA as a function of the oxide film thickness, three different CoO(111) film thicknesses were explored: films of about 20 bilayers (BLs) (approximately 5 nm), 2 BLs, and 1 BL. The two carboxylic acid groups of BDA offer two potential anchoring points to the oxide surface. At 150 K, intact BDA adsorbs on 20 BL thick oxide films in planar geometry with the phenyl rings aligned parallel to the surface. With decreasing oxide film thickness, we observe an increasing tendency for deprotonation and the formation of flat-lying BDA molecules anchored as dicarboxylates. After saturation of the first monolayer, intact BDA multilayers grow with molecules aligned parallel to the surface. The BDA multilayer desorbs at around 360 K. Completely different growth behavior is observed if BDA is deposited above the multilayer desorption temperature. Initially, doubly deprotonated dicarboxylates are formed by adopting a flat-lying,orientation. With increasing exposure, however, the adsorbate layer transforms into upright standing monocarboxylates. A sharp OH stretching band (3584 cm(-1)) and a blue-shifted CO stretching band (1759 cm(-1)) indicate weakly interacting apical carboxylic acid groups at the vacuum interface. The anchored monocarboxylate phase slowly desorbs in a temperature range of up to 470 K. At higher temperature, a flat-lying doubly deprotonated BDA is formed, which desorbs and decomposes in a temperature range of up to 600 K.

Energy Storage in Strained Organic Molecules: (Spectro)Electrochemical Characterization of Norbornadiene and Quadricyclane - Brummel, Olaf; Besold, Daniel; Döpper, Tibor; Wu, Yanlin; Bochmann, Sebastian; Lazzari, Federica; Waidhas, Fabian; Bauer, Udo; Bachmann, Philipp; Papp, Christian; Steinrück, Hans-Peter; Görling, Andreas; et al. (Chemsuschem, 2016)
We have investigated the electrochemically triggered cycloreversion of quadricyclane (QC) to norbornadiene (NBD), a system that holds the potential to combine both energy storage and conversion in a single molecule. Unambiguous voltammetric traces are obtained for pure NBD and pure QC, the latter a strained polycyclic isomer of the former. The difference in redox potentials is smaller than the energy difference between the neutral molecules. This is owing to a significant energy difference between the corresponding radical cations, as demonstrated by density functional theory (DFT) calculations. The vibrational modes of each pure compound are characterized experimentally in the fingerprint region and identified by DFT methods. Thermal and electrochemical transformations of NBD and QC are monitored insitu by IR spectroelectrochemical methods. The kinetics of the cycloreversion of QC to NBD, which is catalyzed by oxidizing equivalents, can be controlled by an applied electrode potential, which implies the ability to adjust in real time the release of thermal power stored in QC.
Keywords: Infrared spectroscopy; Norbornadiene; Quadricyclane; Spectroelectrochemistry; Voltammetry

Functionalized Porphyrins on an Atomically Defined Oxide Surface: Anchoring and Coverage-Dependent Reorientation of MCTPP on Co3O4(111) - Werner, Kristin; Mohr, Susanne; Schwarz, Matthias; Xu, Tao; Amende, Maximilian; Döpper, Tibor; Görling, Andreas; Libuda, Jörg (Journal of Physical Chemistry Letters, 2016)
We have studied the adsorption of tetraphenylporphyrin (2HTPP) and its carboxylated counterpart mono-para-carboxyphenyltriphenylporphyrin (MCTPP) on an atomically defined CoO(111) film under ultrahigh vacuum (UHV) conditions. Using time-resolved infrared reflection absorption spectroscopy (TR-IRAS), we show that 2HTPP adsorbs molecularly in a flat-lying orientation, whereas MCTPP binds to the surface via formation of a chelating bidentate carboxylate upon deposition at 400 K. Combining TR-IRAS and density-functional theory (DFT), we determine the molecular tilting angle as a function of coverage. We show that the MCTPP adsorption geometry changes from a nearly flat-lying orientation (tilting angle <30°) at low coverage to a nearly perfectly upright-standing orientation (tilting angle of approximately 80°) in the full monolayer.

Gas-Phase Transformation of Fluorinated Benzoporphyrins to Porphyrin-Embedded Conical Nanocarbons - Lungerich, Dominik; Hitzenberger, Jakob; Ruppel, Michael; Döpper, Tibor; Witt, Matthias; Ivanovic-Burmazovic, Ivana; Görling, Andreas; Jux, Norbert; Drewello, Thomas (Chemistry - A European Journal, 2020)
Geodesic nitrogen-containing graphene fragments are interesting candidates for various material applications, but the available synthetic protocols, which need to overcome intrinsic strain energy during the formation of the bowl-shaped skeletons, are often incompatible with heteroatom-embedded structures. Through this mass spectrometry-based gas-phase study, we show by means of collision-induced dissociation experiments and supported by density functional theory calculations, the first evidence for the formation of a porphyrin-embedded conical nanocarbon. The influences of metalation and functionalization of the used tetrabenzoporphyrins have been investigated, which revealed different cyclization efficiencies, different ionization possibilities, and a variation of the dissociation pathway. Our results suggest a stepwise process for HF elimination from the fjord region, which supports a selective pathway towards bent nitrogen-containing graphene fragments.
CRIS-Team Scopus Importer:2020-09-11
Keywords: annulenes; collision-induced dissociation; C−F activation; mass spectrometry; polycyclic aromatic hydrocarbons; porphyrinoids

Model Catalytic Studies of Novel Liquid Organic Hydrogen Carriers: Indole, Indoline and Octahydroindole on Pt(111) - Schwarz, Matthias; Bachmann, Philipp; Nascimento Silva, Thais; Mohr, Susanne; Scheuermeyer, Marlene; Späth, Florian; Bauer, Udo; Düll, Fabian; Steinhauer, Johann; Hohner, Chantal; Döpper, Tibor; Noei, Heshmat; et al. (Chemistry - A European Journal, 2017)
Indole derivatives were recently proposed as potential liquid organic hydrogen carriers (LOHC) for storage of renewable energies. In this work, we have investigated the adsorption, dehydrogenation and degradation mechanisms in the indole/indoline/octahydroindole system on Pt(111). We have combined infrared reflection absorption spectroscopy (IRAS), X-ray photoelectron spectroscopy (XPS) and DFT calculations. Indole multilayers show a crystallization transition at 200 K, in which the molecules adopt a strongly tilted orientation, before the multilayer desorbs at 220 K. For indoline, a less pronounced restructuring transition occurs at 150 K and multilayer desorption is observed at 200 K. Octahydroindole multilayers desorb already at 185 K, without any indication for restructuring. Adsorbed monolayers of all three compounds are stable up to room temperature and undergo deprotonation at the NH bond above 300 K. For indoline, the reaction is followed by partial dehydrogenation at the 5-membered ring, leading to the formation of a flat-lying di-sigma-indolide in the temperature range from 330-390 K. Noteworthy, the same surface intermediate is formed from indole. In contrast, the reaction of octahydroindole with Pt(111) leads to the formation of a different intermediate, which originates from partial dehydrogenation of the 6-membered ring. Above 390 K, all three compounds again form the same strongly dehydrogenated and partially decomposed surface species.
Keywords: density functional theory; infrared reflection absorption spectroscopy; liquid organic hydrogen carrier; octahydroindole; X-ray photoelectron spectroscopy

Molecular Orientation and Structural Transformations in Phthalic Anhydride Thin Films on MgO(100)/Ag(100) - Mohr, Susanne; Xu, Tao; Döpper, Tibor; Laurin, Mathias; Görling, Andreas; Libuda, Jörg (Langmuir, 2015)
Structural control of organic thin films on dielectric substrates is the key to tailoring the. physical properties of hybrid Materials, for example, for application in solar energy conversion, molecular electronics, or catalysis. In, this work, we investigate the molecular orientation of phthalic: anhydride (PAA) films on atomically well-defined mgO(100) on Ag(100) using temperature-programmed infrared reflection absorption spectroscopy (TP-IRAS) in combination with density-functional theory (DFT). A robust procedure is presented to determine the orientation of the FAA Molecules, which relies on the intensity ratios of vibrational bands only We show that even at deposition temperatures of 110 K, the PAA multilayer grows with a-Specific molecular, orientation; that is the PAA Molecular plane is preferentially aligned parallel with the MgO surface,. No change of molecular orientation occurs up to a temperature of 145 K Between 145 and 160 K, the film restructures adopting a nearly flat lying molecular Orientation. Between 170 and 205 K, the film undergoes a second structural transition to a crystalline phase. This transition is associated with a pronounced molecular reorientation. The molecules adopt a tilted orientation and, simultaneously, rotate around their C-2 axes The reorientation behavior Suggests that the molecular orientation in the crystalline phase is controlled by the interaction with the MgO(100) substrate. At higher temperature, no further restructuring is observed until the PAA. multilayer desorbs at temperatures above 230 K.

Organic linkers on oxide surfaces: Adsorption and chemical bonding of phthalic anhydride on MgO(100) - Mohr, Susanne; Döpper, Tibor; Xu, Tao; Tariq, Quratulain; Lytken, Ole; Laurin, Mathias; Steinrück, Hans-Peter; Görling, Andreas; Libuda, Jörg (Surface Science, 2016)
To elucidate the adsorption behavior and interaction mechanisms of organic linker units on oxide surfaces, we have performed a model study under ultrahigh vacuum (UHV) conditions. We apply infrared reflection absorption spectroscopy (IRAS) in combination with density-functional theory (DFT), temperature programmed desorption (TPD), and X-ray photoelectron spectroscopy (XPS). Phthalic anhydride (PM) was deposited at temperatures between 100 and 300 K by physical vapor deposition (PVD) onto an ordered MgO(100) film grown on Ag(100). At 100 K, the first monolayer adsorbs molecularly with the molecular plane aligned parallel to the surface. Subsequent growth of a multilayer film at low temperature also occurs with preferential molecular alignment parallel to the surface. At 240 K, the multilayer desorbs without decomposition. At 300 K, a mixed monolayer of chemically modified ring-opened and intact phthalic anhydride exists on the surface. The chemically modified species binds in a strongly tilted geometry via opening of the anhydride ring to form a bis-carboxylate species. This species additionally stabilizes the coadsorbed molecular PM via intermolecular interactions. Finally, surface defects and hydroxyl groups are found to increase the amount of surface bis-carboxylate at 300 K, whereas the relative amount of coadsorbed molecular PAA decreases. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Phthalic anhydride; Magnesium oxide; Organic thin films; Infrared reflection absorption spectroscopy; Density-functional theory

Palladium-Mediated Ethylation of the Imidazolium Cation Monitored In Operando on a Solid Catalyst with Ionic Liquid Layer - Bauer, Tanja; Hager, Veit; Williams, Marc; Laurin, Mathias; Döpper, Tibor; Görling, Andreas; Szesni, Normen; Wasserscheid, Peter; Haumann, Marco; Libuda, Jörg (ChemCatChem, 2017)
The ionic liquid 1-ethyl-3-methylimidazolium ethylsulfate [EMIM][EtOSO] was supported on Pd-AlO to yield a solid catalyst with ionic liquid layer (SCILL) material. During the hydrogenation of ethene, it was found that ethene was incorporated into the imidazolium moiety in a reaction catalyzed by the palladium surface. The formation of 1,2-diethyl-3-methylimidazolium ethylsulfate was confirmed ex situ by means of NMR spectroscopy. Moreover, the reaction itself could be monitored in situ by diffuse reflection infrared Fourier transformation (DRIFT) spectroscopy. A reaction mechanism involving surface carbene species was proposed on the basis of the analytical data.
Keywords: carbenes; heterogeneous catalysis; ionic liquids; palladium; reaction mechanisms

Phosphonic Acids on an Atomically Defined Oxide Surface: The Binding Motif Changes with Surface Coverage - Schuschke, Christian; Schwarz, Matthias; Hohner, Chantal; Silva, Thais N.; Fromm, Lukas; Döpper, Tibor; Görling, Andreas; Libuda, Jörg (Journal of Physical Chemistry Letters, 2018)
We have studied the anchoring mechanism of a phosphonic acid on an atomically defined oxide surface. Using time-resolved infrared reflection absorption spectroscopy, we investigated the reaction of deuterated phenylphosphonic acid (DPPA, C6HsPO3D2) with an atomically defined Co3O4(111) surface in situ during film growth by physical vapor deposition. We show that the binding motif of the phosphonate anchor group changes as a function of coverage. At low coverage, DPPA binds in the form of a chelating tridentate phosphonate, while a transition to a chelating bidentate occurs close to monolayer saturation coverage. However, the coverage-dependent change in the binding motif is not associated with a major change of the molecular orientation, suggesting that the rigid phosphonate linker always maintains the DPPA in a strongly tilted orientation irrespective of the surface coverage.

ZnO Nanoparticle Formation from the Molecular Precursor [MeZnOtBu](4) by Ozone Treatment in Ionic Liquids: in-situ Vibrational Spectroscopy in an Ultrahigh Vacuum Environment - Bauer, Tanja; Voggenreiter, Markus; Xu, Tao; Wähler, Tobias; Agel, Friederike; Pohako-Esko, Kaija; Schulz, Peter; Döpper, Tibor; Görling, Andreas; Polarz, Sebastian; Wasserscheid, Peter; Libuda, Jörg (Zeitschrift für Anorganische und Allgemeine Chemie, 2017)
As reported previously, novel ZnO nanostructures can be grown by oxidation of [MeZnOtBu](4) building blocks with O-3 in ionic liquids (ILs). In this study, we have explored the role of the IL during ZnO formation by in-situ infrared reflection absorption spectroscopy (IRAS) in ultrahigh vacuum (UHV). [MeZnOtBu](4) and [C(2)C(1)Im][OTf] were (co-)deposited as thin films by physical vapor deposition (PVD) onto Au(111), separately or simultaneously. The IR spectrum of [MeZnOtBu](4) was analyzed between 300 and 4000 cm(-1) based on calculated spectra from density-functional theory (DFT). Spectral changes in the IL-related bands during the thermal treatment of [MeZnOtBu](4) in [C(2)C(1)Im][OTf] indicate the loss of the precursor ligands and the interaction of the IL with the growing ZnO aggregates. The films were treated with ozone (10(-6) mbar) in UHV and the spectral changes were monitored in-situ by IRAS. Slow ozonolysis of [C(2)C(1)Im][OTf] is observed. Spectroscopically we identify the primary ozonide formed by addition of O-3 to [C(2)C(1)Im](+) and suggest a reaction mechanism, which leads to a biuret derivative. Upon ozone treatment of mixed [MeZnOtBu](4)/[C(2)C(1)Im][OTf] films, ZnO aggregates are formed at the IL/vacuum interface. Ozonolysis of [C(2)C(1)Im][OTf] is suppressed. Upon annealing to 320 K, further ZnO aggregates are formed, leading to enclosure of [C(2)C(1)Im][OTf] in the ZnO film. At 380 K the IL is released from the mixed film. The pure [C(2)C(1)Im][OTf] desorbs at 420 K, leaving behind the ZnO phase.
Keywords: Ionic liquid; Ozone; IR spectroscopy; ZnO nanoparticles; Surface science

ZnO Nanoparticle Formation from the Molecular Precursor [MeZnOtBu]4 by Ozone Treatment in Ionic Liquids: in-situ Vibrational Spectroscopy in an Ultrahigh Vacuum Environment - Bauer, Tanja; Voggenreiter, Markus; Xu, Tao; Wähler, Tobias; Agel, Friederike; Pohako-Esko, Kaija; Schulz, Peter; Döpper, Tibor; Görling, Andreas; Polarz, Sebastian; Wasserscheid, Peter; Libuda, Jörg (Zeitschrift für Anorganische und Allgemeine Chemie, 2017)
As reported previously, novel ZnO nanostructures can be grown by oxidation of [MeZnOtBu]“building blocks” with Oin ionic liquids (ILs). In this study, we have explored the role of the IL during ZnO formation by in-situ infrared reflection absorption spectroscopy (IRAS) in ultrahigh vacuum (UHV). [MeZnOtBu]and [CCIm][OTf] were (co-)deposited as thin films by physical vapor deposition (PVD) onto Au(111), separately or simultaneously. The IR spectrum of [MeZnOtBu]was analyzed between 300 and 4000 cmbased on calculated spectra from density-functional theory (DFT). Spectral changes in the IL-related bands during the thermal treatment of [MeZnOtBu]in [CCIm][OTf] indicate the loss of the precursor ligands and the interaction of the IL with the growing ZnO aggregates. The films were treated with ozone (10mbar) in UHV and the spectral changes were monitored in-situ by IRAS. Slow ozonolysis of [CCIm][OTf] is observed. Spectroscopically we identify the primary ozonide formed by addition of Oto [CCIm]and suggest a reaction mechanism, which leads to a biuret derivative. Upon ozone treatment of mixed [MeZnOtBu]/[CCIm][OTf] films, ZnO aggregates are formed at the IL/vacuum interface. Ozonolysis of [CCIm][OTf] is suppressed. Upon annealing to 320 K, further ZnO aggregates are formed, leading to enclosure of [CCIm][OTf] in the ZnO film. At 380 K the IL is released from the mixed film. The pure [CCIm][OTf] desorbs at 420 K, leaving behind the ZnO phase.
Keywords: Ionic liquid; Ozone; IR spectroscopy; ZnO nanoparticles; Surface science